The Paradox of Legislative Performance: Human Resource Capacity and Executive Dominance in the Regional People’s Representative Council of Teluk Bintuni Regency - Charlos G Maay; Muhammad Irvan Nur Iva; Herman H; Andi Kasmawati; Didik Iskandar (ASHA Publishing, 2026)
This study examines the paradox of legislative performance in the Regional People’s Representative Council of Teluk Bintuni Regency during the 2021–2024 period, where increasing legislative output does not necessarily reflect stronger institutional capacity or independence. This study uses a qualitative case study approach to examine legislative performance in the Regional People’s Representative Council of Teluk Bintuni Regency. Data were collected through in-depth interviews, observation, and document analysis involving council members, secretariat staff, and representatives of the regional government. Data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing, to identify patterns related to human resource capacity, executive dominance, and legislative performance. The findings show that legislative performance reflects a combination of increasing output and persistent structural constraints. The realization of the Regional Legislation Program demonstrates a generally rising trend, indicating improved legislative productivity. However, the majority of council members have a secondary education background, which reflects limited formal capacity in legislative functions. In addition, the executive dominates the legislative process, as indicated by the high proportion of draft regulations initiated and prepared by the executive. Institutional coordination is formally established but uneven in effectiveness, while public participation mechanisms remain limited and not consistently institutionalized. This study concludes that legislative performance is characterized by a paradox in which improvements in quantitative output are not accompanied by stronger institutional capacity or independence. These findings highlight the need to move beyond output-based assessments and to consider structural and relational factors in understanding legislative performance in decentralized governance systems.